Ethnomathematics Study at The Tomb of Sunan Bonang Tuban - Warli, Warli; Alfiyah, Khusnul (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2024)
Ethnomathematics is mathematics inherent in the form of local wisdom. This study aims to describe the ethnomathematics at the Tomb of Sunan Bonang Tuban. These Data were obtained through observation, interviews, and documentation. The Data is analyzed by reducing the data, presenting the data, and drawing conclusions. To obtain the validity of the data, a credibility test through triangulation, a transferability test through a detailed description, as well as a dependability test and confirmability test by auditing. The results of ethnomathematics studies on the Tomb of Sunan Bonang Tuban in the aspect of counting there candra sengkala on gate I. In the aspect of locating obtained patterns of sequential arrangement of pages, the arrangement of pages and gates that have a repeating pattern, the arrangement of Pendopo rante sirap and Sunan Bonang Tomb cungkup sirap that form an arithmetic sequence, the arrangement of cemaric plates on the rana that form a pattern of numbers, and the arrangement of other tombs are parallel. In designing aspects obtained page I and III rectangular, trapezoidal page II, shingle Pavilion rante and Sunan Bonang Tomb cungkup-shaped combination of rectangular pyramid and truncated rectangular pyramid.